Clinical characteristics and factors associated with triple therapy use in newly diagnosed patients with COPD - Mònica Monteagudo (Nature Portfolio, 2021)
Abstract There is limited information about the initiation of triple therapy (TT) in patients with chronic obstructive pulmonary disease (COPD) in primary care. This was an observational, population-based study in patients identified from a primary care electronic medical records database in Catalonia from 2011 to 2015 aimed to identify the use of TT in patients with newly diagnosed COPD. A total of 69,668 newly diagnosed patients were identified of whom 11,524 (16.5%) initiated TT, of whom 8626 initiated TT at or immediately after COPD diagnosis. Among them, 72.3% were GOLD A/B, 14.6% were frequent exacerbators, and 7.1% had asthma–COPD overlap (ACO). Variables associated with TT initiation were: male sex, older age, previous exacerbations, ACO, a previous treatment regimen containing an inhaled corticosteroid, previous pneumonia, and history of lung cancer. A significant number of COPD patients in Primary Care initiated TT shortly after or even before an established COPD diagnosis.